Creating English Articles about Kayutangan Heritage for Tugu Jatim - Kautsar, Rizal; Setiawan, Ardian Wahyu; Sakinah, Yanik Lalinas (Kirana Publisher (KNPub), 2024)
This research aimed to develop seven English articles about Kayutangan Heritage for Tugu Jatim to address the lack of English tourism content on the Tugu Jatim website. The purpose of this research was to increase the number of English articles on the Tugu Jatim’s tourism channel and align with Tugu Jatim's